Stability of an acid activated carbon based bifunctional catalyst for the raw bio-oil hydrodeoxygenation - Cordero-Lanzac, Tomás; Palos, Roberto; Arandes, José M.; Castaño, Pedro; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás; Bilbao, Javier (Elsevier, 2017)
The performance (activity, selectivity and stability) of a Pt-Pd catalyst supported on a phosphorus-containing activated carbon (ACP) has been studied in the hydrodeoxygenation (HDO) of raw bio-oil, and compared with another bifunctional catalyst prepared with a FCC (Fluid Catalytic Cracking) catalyst as acid support. Experiments have been carried out in a fixed bed reactor under the following conditions: 400–450 °C; 65 bar; space time, 0.18 gcat h g−1bio-oil; H2:bio-oil ratio, 20 cm3H2 (STP) cm−3bio-oil; time on stream, 0–10 h. The catalyst reaches a pseudo-steady state at 450 °C after 6 h of time on stream, preserving a constant activity as a consequence of the simultaneous formation and hydrocracking of the deposited coke. In these conditions, the yield of C5+ hydrocarbons is 20 wt%. This organic liquid fraction mainly contains aromatics, and thus, it may require an additional mild hydrocracking treatment for its valorization as fuel. On the other hand, the gas fraction obtained can be used directly as fuel, and the aqueous liquid fraction (with a high concentration of methanol, 58 wt%) is interesting as co-feedstock with methanol in a methanol to olefins (MTO) unit.
Keywords: Carbón activado; Bio-Oil; Catalizadores Pt-Pd; Carbones activos; Desactivación; Ingeniería Química